Spatial distribution patterns of the non-native European catfish, Silurus glanis, from multiple onlinesources : a case study for the River Tagus (IberianPeninsula) - Gago, João (2016)
Effective management of invasive fishes depends on the availability of updated information about their distribution and spatial dispersion. Forensic analysis was performed using online and published data on the European catfish, Silurus glanis L., a recent invader in the Tagus catchment (Iberian Peninsula). Eighty records were obtained mainly from anglers’ fora and blogs, and more recently from www.youtube.com. Since the first record in 1998, S. glanis expanded its geographic range by ≈700 km of river network, occurring mainly in reservoirs and in high-order reaches. Human-mediated and natural dispersal events were identified, with the former occurring during the first years of invasion and involving movements of >50 km. Downstream dispersal directionality was predominant. The analysis of online data from anglers was found to provide useful information on the distribution and dispersal patterns of this non-native fish, and is potentially applicable as a preliminary, exploratory assessment tool for other non-native fishes.